Auditor’s Quality in Bali Provincial Representative of Supreme Audit Agency in Denpasar - Ni Nyoman Ari Novarini, SE,MM Putu; Desak Ayu Sriary Bhegawati (Advances in Global Economics and Business Journal, 2020)
Planning strategies for state and regional development are still lacking due to misappropriation of public fund, corruption, and the absence of honesty and transparency in governance finances of a state and a region. This demands noticeable improvements. Thus, audit quality is highly vital for public accounting firms. Public accountants have the duty and function of auditing financial statements by producing accurate, and reliable audit reports. This study discusses audit quality of Bali Provincial Supreme Audit Agency auditors in Denpasar. The data are primary data, collected from 50 auditors, as saturated sample of respondents, in Bali Provincial Representative Office. The data were then analyzed by multiple linear regression analysis. This paper research contended that independence, professional expertise, and professional ethical sensitivity have positive and significant effects on audit quality at the Supreme Audit Agency.